Development of a QR Code-Based Opinion Survey System Using AI and Cloud Technology for Predictive Analysis in Product and Service Development - เป็กเยียน ธณพิชญ์; หล่อนิล ณัฐพล; เกตุษา ชุติมา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to develop a system for collecting and analyzing consumer opinions through QR codes by leveraging artificial intelligence (AI) and cloud computing technologies for real-time data processing. The proposed system enables entrepreneurs to gain a deeper understanding of customer needs and behavioral trends more effectively. It supports satisfaction evaluation and predictive behavior modeling using machine learning algorithms, with results presented via an interactive dashboard. The system was tested among community enterprises and small and medium-sized enterprises (SMEs), demonstrating a reduction in data collection time and costs by over 60%, and an improvement in analytical accuracy by up to 85%. These outcomes highlight the potential of the system to drive sustainable growth in grassroots economies and local businesses.